(3GdLhGHGJ GdhGajI HGdHQGgjf GdTGajIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3UdGM Hf eMeO Hf UdGM Hf Ydi Hf GdMSjf Hf YHO Gddg Hf jMji Hf MeRI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ChQOfG MHkG ai GdeYQaI CeG HYO aMb Ydi ef efMg Gddg ai GdYde HUjQI fYe hUdJfG eSGFd ef TNU CVeQ ajgG faSg hZGdH GdXf Cf GdSGFd YfgG s
(3BNQgG (B:s
(3aEf JUQa GdCUhdi ai GdeSGFd GdabgjI ebHhd egeG CSfO GdbjGS , hcGf LGQjkG Ydi CUhdg , hde jNGda ELeGYkG agPG eG CQOfG PcQg ai gPg GdeSGFd Ydi egeI GdGNJUGQ s
(3GdfSNI HgG MhGTs
(3fSNI eUMMIs
(3cJHJ GdahGJM GdSejc s
(3fbdJ ef fSNI cJHJ SfI (B732 (3g` s
(3hjHOh Cf GdfSNI CcedJ HNW MOjK SfI (B1337 (3g` s
(3hgj HQSe NRGfI LeGd GdOjf Gdhdi Hf YHO Gddg GdMSfi s
Keywords: (3Gdabg GdESdGejs